Karakteristik Habitat Siput Gonggong Strombus turturella di Ekosistem Padang Lamun - Okto Supratman; Tati Suryati Syamsudin; Okto Supratman (Universitas Diponegoro, 2018)
Characteristic of Dog Conch Strombus turturella Habitat on The Seagrass Ecosystem Strombus turturella or commonly known as dog conch is one of marine shellfish which has important ecological role, as well as high economical value as fisheries commodity. The objectives of the study were to determine the density and biomass of the shellfish, as well as to observe the distribution pattern and the characteristics of dog conch habitat in the seagrass ecosystem. The research was conducted at Tukak Island and Anak Air Island, Bangka Belitung Islands. Density of the shellfish, seagrass coverage, seagrass density as well as water chemistry and physical parameters, while data collection in laboratory, measurement of dog conch biomass, substrate texture test and organic matter content. Habitat characteristics were determined using principal component analysis (PCA), which connects between dog conch density variables, seagrass vegetation and chemical physics parameters. The average density of dog conch in all locations is 2312 ind / ha. The pattern of distribution of dog conch at the study site there is a pattern of uniform distribution and clumping, but the overall pattern of distribution is clustering. The PCA results show dog conch, with habitat characteristics that is very low seagrass cover (1-5%), overgrown species of Halophila minor seagrass, with the condition of muddy sand substrate and low content of organic matter. Result of the correlation matrix dog conch was correlated with H. Minor seagrass (0.88), very low seagrass cover (0.86) and muddy sand substrate (0.9). This is aimed at dog conch keeping specific microhabitat in the seagrass ecosystem. Siput gonggong memiliki peranan ekologis yang penting di habitatnya. Nilai ekonomis siput gonggong yang tinggi sebagai komoditas perikanan telah menyebabkan eksploitasi berlebihan terhadap spesies tersebut. Tujuan penelitian yaitu 1)menentukan kepadatan dan biomassa siput gonggong, 2)Pola sebaran dan 3)Karakteristik habitat siput gonggong di ekosistem padang lamun. Penelitian dilakukan di Pesisir Tukak dan Pulau Anak Air, Kepulauaan Bangka Belitung. Pengambilan data di lapangan melputi pengukuran kepadatan, perhitungan tutupan lamun, kerapatan lamun dan pengukuran parameter fisika kimia perairan, sedangkan pengambilan data di laboratorium meiputi, pengukuran biomassa siput gonggong, uji tekstur substrat dan kandungan bahan organik. Karakteristik habitat ditentukan menggunakan analisis komponen utama (PCA), yang menghubungkan antar variabel kepadatan siput gonggong, vegetasi lamun dan parameter fisika kimia perairan. Kepadatan rata-rata siput gonggong di semua stasiun yaitu 2312 ind/ha. Pola sebaran siput gonggong di stasiun penelitian ada pola sebaran seragam dan mengelompok, tetapi secara keseluruhan pola sebaran yaitu mengelompok. Hasil PCA menujukan siput gonggong, dengan karakteristik habitat yaitu tutupan lamun sangat rendah (1-5 %), ditumbuhi spesies lamun Halophila minor, dengan kondisi substrat pasir berlumpur dan rendah kandungan bahan organik. Selain itu berdasarkan hasil matrik korelasi bagian dari output PCA siput gonggong berkorelasi positif dengan lamun H. Minor (0,88), tutupan lamun sangat rendah (0,86) dan substrat pasir berlumpur (0,9). Hal ini menujukan siput gonggong menepati mikrohabitat yang spesifik di ekosistem padang lamun.